Effect of Exclusive Breastfeeding on the Risk of ARI in Under-Five Children: Literature Review - Khansa Khairunnisa; Lucia Yovita Hendrati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Acute Respiratory Infection (ARI) is a major health problem in under-five children which can cause death. Exclusive breastfeeding can prevent infections, one of which is ARI. Objective: This study aims to examine the relationship between exclusive breastfeeding and the risk of ARI in under-five children. Method: This research uses a literature review approach which measures the relationship between exclusive breastfeeding and the risk of ARI in under-five children. The data source uses secondary data in the form of articles obtained through two databases, namely Scopus and Springer Link. Result: There are 5 articles that meet the requirements for research. Four out of five articles prove that exclusive breastfeeding reduces the risk of children under five getting ARI. The finding of a higher risk of ARI in the group of children under five who are not exclusively breastfed can be caused by a decrease in the immunity of children under five, seeing that breast milk is proven to fight infection. The content of sIgA and lactoferrin in breast milk and immunization can increase the immune system in children under five who suffer from ARI. Conclusion: Breast milk has nutrients in it which are useful for preventing infectious diseases, such as ARI and pneumonia in children under five. Given the influence on the health of children under five, the findings of this study demonstrate the need for improvements in breastfeeding programs, with a particular emphasis on exclusive breastfeeding and ARI management. There is a need for widely accessible health workers, information, and services connected to care for moms.